PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP EFISIENSI INVESTASI - Fajri Yudha; Annisaa Rahman (Faculty of Economics and Business, Universitas Warmadewa, 2024)
This research aims to test and analyze the influence of ESG disclosure both in aggregate and the influence of partial ESG components consisting of environmental, social and corporate governance disclosures on investment efficiency in companies listed on the IDX for the 2017-2021 period. Data collection in this research used the documentation method. This research uses purposive sampling as a sampling method with a total sample of 210 companies listed on the IDX. The results of this study show that aggregate ESG disclosure has a positive effect on investment efficiency. Meanwhile, partial ESG disclosure has no influence on investment efficiency. The findings of this research provide important awareness to companies regarding the benefits of carrying out comprehensive ESG disclosures.